2007
DOI: 10.2306/scienceasia1513-1874.2007.33.079
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Continuing increases in atmospheric carbon dioxide concentration, [CO 2 ], will likely be accompanied by global warming. Thus, it is important to quantify and understand the consequences of elevated [CO 2 ] and temperature on crop growth and yield to develop suitable varieties and agronomic management practices for future climates. The objective of this study was to investigate the growth and development responses of shoots and roots of peanut (Arachis hypogaea L.) grown under different combinations of atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Temperature and CO 2 effects were studied in groundnut and total root length increased with increasing CO 2 from 400 to 800 μmol mol -1 at both low and high temperatures (Pilumwong et al, 2007). Although the difference was not significant, there was an observed increase of 13% when plants were grown at 600 μmol mol -1 CO 2 , and 20% at 800 μmol mol -1 CO 2 .…”
Section: Root Length and Rooting Depthmentioning
confidence: 94%
See 3 more Smart Citations
“…Temperature and CO 2 effects were studied in groundnut and total root length increased with increasing CO 2 from 400 to 800 μmol mol -1 at both low and high temperatures (Pilumwong et al, 2007). Although the difference was not significant, there was an observed increase of 13% when plants were grown at 600 μmol mol -1 CO 2 , and 20% at 800 μmol mol -1 CO 2 .…”
Section: Root Length and Rooting Depthmentioning
confidence: 94%
“…In maize (Zea mays L.) grown under elevated CO 2 relative growth rate of maize roots was increased compared to the relative shoot growth rate (Whipps, 1985) because of increased C translocation to the roots. Pilumwong et al (2007) reported increased root growth of groundnut due to increasing CO 2 concentration. With no limitations to water and nutrients, elevated CO 2 increased root and shoot growth of most plant species including tree species (Obrist and Arnone, 2003;Rogers et al, 1996;Pregitzer et al,1995) but the response varied among species (Hanley et al, 2004).…”
Section: Root Biomassmentioning
confidence: 98%
See 2 more Smart Citations
“…According to the results of the Tukey-Kramer's test, vigour index I and vigour index II exhibited the same trend in Enshikei 6; that is, both vigour indexes had significantly have reported that elevated [CO 2 ] stimulates the growth of both shoots and roots (Conn & Cochran, 2006;Pilumwong et al, 2007;Usuda & Shimogawara, 1998;Ziska et al, 1997). However, the allocation of biomass to shoots and roots in crops under elevated [CO 2 ] may be different from that under ambient [CO 2 ] under certain conditions.…”
Section: Discussionmentioning
confidence: 92%